Anthrax: Where margins are merging between emerging threats and bioterrorism - Dibyendu Banerjee; Baishali Chakraborty; Banya Chakraborty (Wolters Kluwer Medknow Publications, 2017)
National Institute of Allergy and Infectious Diseases has classified all the emerging infectious diseases agents under three categories. Among Category A priority pathogens comes Bacillus anthracis -the causative agent of Anthrax. It is a gram positive spore bearing bacteria, and the disease is typically associated with grazing animals, and affects the people as a zoonosis. The disease can be classically transmitted by three routes namely: cutaneous, gastrointestinal and pulmonary, with a fourth route recently identified as "injection anthrax", seen in intravenous drug abusers. Cutaneous anthrax is the commonest form in humans, accounting for 95% of all the cases. There are two main virulence factors of this bacteria, a capsule and an exotoxin, each carried by a separate toxin. Two models have been used for explaining the pathogenesis of this infection. The earlier one or "Trojan horse" model is now replaced with "jail-break" model. Centers for disease control (CDC) has issued updated guidelines for diagnosis, post-exposure prophylaxis and treatment. For immunization, anthrax vaccine absorbed is available.